Erving Goffman et le travail social - Namian, Dahlia, 1979-; Garneau, Stéphanie, 1975- (21e--société, histoire et culture., 2017)
As disciplines become increasingly fragmented and compartmentalized, it is imperative to call to mind the ambiguous yet intertwined connections between social work and the sociological tradition in which Erving Goffman was trained. The authors of this work--social workers, sociologists, anthropologists, political scientists and nurses--open the "Goffman toolbox" to offer fresh perspectives on contemporary social work issues. The work focuses on a wide range of topics, including mental health, addiction, care for the elderly or persons with a disability and homelessness. Whether through an epistemological, theoretical, methodological or practical lens, the Goffmanian point of view is worthy of consideration. It suggests a way of observing the effects of institutions and social work categories on individuals. It goes beyond social workers' normative vision to identify the possibilities and restrictions they face. Finally, it accesses tacit, affective and sometimes unsuspected dimensions of the social question and of helping relationships, rendering visible what is not and intolerable, what is indeed tolerated. The seventeen contributors strive to bridge the gap that developed between the two disciplines as they struggled for institutional recognition.